Sulfur isotope's signal of nanopyrites enclosed in 2.7 Ga stromatolitic organic remains reveal microbial sulfate reduction. Issue 2 (30th January 2018) - Marin‐Carbonne, J.; Remusat, L.; Sforna, M. C.; Thomazo, C.; Cartigny, P.; Philippot, P.
Abstract: Microbial sulfate reduction (MSR) is thought to have operated very early on Earth and is often invoked to explain the occurrence of sedimentary sulfides in the rock record. Sedimentary sulfides can also form from sulfides produced abiotically during late diagenesis or metamorphism. As both biotic and abiotic processes contribute to the bulk of sedimentary sulfides, tracing back the original microbial signature from the earliest Earth record is challenging. We present in situ sulfur isotope data from nanopyrites occurring in carbonaceous remains lining the domical shape of stromatolite knobs of the 2.7‐Gyr‐old Tumbiana Formation (Western Australia). The analyzed nanopyrites show a large range of δ 34 S values of about 84‰ (from −33.7‰ to +50.4‰). The recognition that a large δ 34 S range of 80‰ is found in individual carbonaceous‐rich layers support the interpretation that the nanopyrites were formed in microbial mats through MSR by a Rayleigh distillation process during early diagenesis. An active microbial cycling of sulfur during formation of the stromatolite may have facilitated the mixing of different sulfur pools (atmospheric and hydrothermal) and explain the weak mass independent signature (MIF‐S) recorded in the Tumbiana Formation. These results confirm that MSR participated actively to the biogeochemical cycling of sulfur during the Neoarchean and support previous models suggesting anaerobic oxidation of methane using sulfate in the Tumbiana environment.